Implementasi Metode Simple Additive Weighting Dalam Penentuan Bantuan Dana Covid . - Dwi marisa Efendi; Asep Afandi; Ferly Ardhy (Prosiding SISFOTEK, 2020)
Covid pandemic is happening at Indonesian, expecially at lampung.it makes regional goverments needs a system Decision Making System used to determination covid help. Method used is saw. This method uses multiple criteria.Criterias are profesion, land living, electricity, water, fuel, income, floor type, building area. SPK is used to avoid subjectively granting assistance.error value is 0,009043027